Can the Trade-off Theory Explain Debt Structure? - Hackbarth, Dirk; Hennessy, Christopher A.; Leland, Hayne E. (Review of Financial Studies, 2007)
We examine the optimal mixture and priority structure of bank and market debt using a trade-off model in which banks have the unique ability to renegotiate outside formal bankruptcy. Flexible bank debt offers a superior trade-off between tax shields and bankruptcy costs. Ease of renegotiation limits bank debt capacity, however. Optimal debt structure hinges upon which party has bargaining power in private workouts. Weak firms have high bank debt capacity and utilize bank debt exclusively. Strong firms lever up to their (lower) bank debt capacity, augment with market debt, and place the bank senior. Therefore, the trade-off theory offers an explanation for: (i) why young/small firms use bank debt exclusively; (ii) why large/mature firms employ mixed debt financing; and (iii) why bank debt is senior. The trade-off theory also generates predictions consistent with international evidence. In countries in which the bankruptcy regime entails soft (tough) enforcement of contractual priority, bank debt capacity is low (high), implying greater (less) reliance on market debt.